2017
DOI: 10.1111/nep.12837
|View full text |Cite
|
Sign up to set email alerts
|

Haemodialysis patients with diabetes eat less than those without: A plea for a permissive diet

Abstract: Diabetes is an important factor associated with low dietary intake in haemodialysis patients. Restrictive regimens should be prescribed cautiously in haemodialysis patients, especially in those with diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 24 publications
0
11
0
2
Order By: Relevance
“…And while hypoalbuminemia is more frequently observed among patients with vs. without DM [37], it does not appear to differ between patients with diabetic kidney disease compared to patients with DM as a comorbidity whose renal disease is due to another underlying condition [38]. While there is some disagreement as to the meaning of these findings, investigators have noted that dietary intake is significantly lower in dialysis patients with vs. without DM, suggesting that hypoalbuminemia represents deteriorated nutrition status in these patients [39]. Hypoalbuminemia has long been identified as an independent risk factor for CVD in HD patients [40], though one report identified this association in patients receiving peritoneal dialysis but not in HD patients [41].…”
Section: Discussionmentioning
confidence: 80%
“…And while hypoalbuminemia is more frequently observed among patients with vs. without DM [37], it does not appear to differ between patients with diabetic kidney disease compared to patients with DM as a comorbidity whose renal disease is due to another underlying condition [38]. While there is some disagreement as to the meaning of these findings, investigators have noted that dietary intake is significantly lower in dialysis patients with vs. without DM, suggesting that hypoalbuminemia represents deteriorated nutrition status in these patients [39]. Hypoalbuminemia has long been identified as an independent risk factor for CVD in HD patients [40], though one report identified this association in patients receiving peritoneal dialysis but not in HD patients [41].…”
Section: Discussionmentioning
confidence: 80%
“…The reasons or consequences of these differences are not known and, as most of the previous studies have quite exclusively focused on the dietary intake when renal deterioration has already progressed into end-stage renal disease, comparing these observations with the previous ones is challenging. In one study assessing dietary intake in haemodialysis, lower intakes of total energy, protein, and calcium were reported in individuals with diabetes compared to those without [18]. Another study of haemodialysis reported higher intakes of total energy, protein, fat, and fibre in men with diabetes compared to men without [19].…”
Section: Discussionmentioning
confidence: 99%
“…Diabetologists, nephrologists, and nutritionists should be involved in treating patients with DMCKD who are getting worse, because the exact assessments of the nutritional status of those patients and the proper nutritional interventions for those patients are never easy and simple [14]. Most importantly, dietary advice should be tailored to the individual and the stage of DMCKD.…”
Section: Discussionmentioning
confidence: 99%